2014
DOI: 10.1007/s00253-014-5729-0
|View full text |Cite
|
Sign up to set email alerts
|

Functions of poly-gamma-glutamic acid (γ-PGA) degradation genes in γ-PGA synthesis and cell morphology maintenance

Abstract: Poly-γ-glutamic acid (γ-PGA) is an important biopolymer with greatly potential in industrial and medical applications. In the present study, we constructed a metabolically engineered glutamate-independent Bacillus amyloliquefaciens LL3 strain with considerable γ-PGA production, which was carried out by single, double, and triple markerless deletions of three degradation genes pgdS, ggt, and cwlO. The highest γ-PGA production (7.12 g/L) was obtained from the pgdS and cwlO double-deletion strain NK-pc, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 38 publications
5
51
0
Order By: Relevance
“…The plasmids for gene deletion (pKSV7-ΔsacA, pKSV7-ΔRBAM_031820 and pKSV7-ΔsacTPA) were constructed as previously reported protocols [14]. The gene deletion in this study was carried out following a previously reported marker-less gene deletion method [19, 20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasmids for gene deletion (pKSV7-ΔsacA, pKSV7-ΔRBAM_031820 and pKSV7-ΔsacTPA) were constructed as previously reported protocols [14]. The gene deletion in this study was carried out following a previously reported marker-less gene deletion method [19, 20].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it has been widely used in fields of foods, medicines, cosmetics and agriculture [11]. Bacillus amyloliquefaciens NK-1 strain is a glutamate-independent poly-γ-glutamic acid (γ-PGA) producing strain, and it can use sucrose as the carbon source [1214]. The whole genome of this strain has been sequenced [15].…”
Section: Introductionmentioning
confidence: 99%
“…The gene insertion plasmids pKSV7-P xyl and pKSV7-PO1 were constructed following the previously reported procedures [12]. The NADPH-dependent glutamate dehydrogenase gene from C. glutamicum ATCC13032 was codon optimized to match the Bacillus.…”
Section: Methodsmentioning
confidence: 99%
“…Real‐time PCR analysis for the target genes was performed using the SYBR ® PremixEx Taq TM II (Takara, Dalian, China). Transcript levels of the target genes were normalized against the levels of rspU (Feng, Goa, Gu, Zang, Cao et al., ).…”
Section: Methodsmentioning
confidence: 99%